Heart Rate Variability And Muscle Strength In Young Male Adults With Sedentary Behaviour. - Norsham Juliana; Zolkafi MAA; Azmani S; Abu IF; Mon Sarip NA; Abu Yazit NA; Nur Islami Teng MF; Das S (IIUM, 2024)
Indexed by WOS/SCOPUS/MYCITE